Thermoplastic starch composites with TiO2particles: Preparation, morphology, rheology and mechanical properties - Ostafińska, A; Mikešová, J; Krejčíková, S; Nevoralová, M; Šturcová, A; Zhigunov, A; Michálková, D; Šlouf, M (International journal of biological macromolecules, 2017)
Composites of thermoplastic starch (TPS) with titanium dioxide particles (mTiO2; average size 0.1μm) with very homogeneous matrix and well-dispersed filler were prepared by a two-step method, including solution casting (SC) followed by melt mixing (MM). Light and scanning electron microscopy confirmed that only the two-step procedure (SC+MM) resulted in ideally homogeneous TPS/mTiO2systems. The composites prepared by single-step MM contained non-plasticized starch granules and the composites prepared by single-step SC suffered from mTiO2agglomeration. Dynamic mechanical measurements showed an increase modulus with increasing filler concentration. In TPS containing 3wt.% of mTiO2the stiffness was enhanced by >40%. Further experiments revealed that the recommended addition of chitosan or the exchange of mTiO2for anisometric titanate nanotubes with high aspect ratio did not improve the properties of the composites.
Keywords: titan; Titanium; reologie; Temperature; Rheology; škrob; Starch; Plastics; teplota; mechanické jevy; plastické hmoty; Mechanical Phenomena